PENGEMBANGAN E-MODUL MENGGUNAKAN VIDEO BERBASIS WONDERSHARE FILMORA MATERI TEKS EKSPLANASI UNTUK MENINGKATKAN HASIL BELAJAR - Jaja Sudarjat; Nanda Dwi Lestari; Raden Teti Rostikawati (Bajang Institute, 2025)
The purpose of this study is to develop an e-module using Wondershare Filmora- based video explanatory text material, so that it is feasible to be tested and effective to be able to improve students' learning outcomes. This research method uses the Research and Development (R&D) method with the ADDIE (analysis, design, development, implementation and evaluation) development model. This research involved 30 students and in the process of validation and trial of the e- modules that have been developed. Validation was carried out by validators, namely material experts, teacher subject matter experts, linguists, and media experts, with the validation results of 92% of the subject matter experts, 100% of teacher subject matter experts, 92% of linguists, and media experts of 97% with an average result of 95.25% which was included in the